PERANCANGAN PROMOSI SUBSTANCE BOARDRIDING STORE PADANG MELALUI MEDIA AUDIO VISUAL - SENGKI HANUR PUTRA, Drs. Syafwandi, M.Sn, San Ahdi, S.Sn., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Substance Boardriding Store is a surf or skate shop is addressed at Pondok No. 1 Padang. Promotion conducted by the Substance boardriding store does not reach the target, resulting in a gap of the target audience. During Substance boardriding Store only do promotion through facebook. According to the Substance Boarding store owner, they have not done such a good promotion or interesting as still puzzled by the selection of a media campaign that will be conducted. This is because the target audience is expected by the Substance boardriding store is the target audience who have the courage and ability were high because this sport is quite extreme.Needed a solution to solving the problem, in order to help the Substance boardriding Store in promoting young children's presence in the middle of the city of Padang in particular, the authors try to design a media campaign Substance boardriding Store through audio-visual media in which the output or result of a video anniversary promotion.Therefore, to introduce and expand the range of promotion, which required the design of a new media campaign for Sustance boardriding Store Champaign shaped promotional video, that will aim to introduce Sustance boardriding Store Padang reached the target audience. For the design process starts with data collection, observation, interview and documentation. So the problems that occur in the promotion of Substance boardriding store can be known, from the identification of the problem, by using SWOT analysis.The design resulted in major media in the form of audio-visual packaged in a promotional video featuring impressions Substance boardriding store information Padang. Audio visual promotional use visualization scenes containing about produkdan facility in Padang Substance boardriding store. The main promotional media features supporting media such as CD covers, CD labels, posters, stickers, id cards, pin, card members, and the x-banners.Keyword: Audio Visual Media, promotion, Subsatance boardriding Store Padang, Through Audio Visual Media.